The Anti-inflammatory Effects of Short Chain Fatty Acids on Lipopolysaccharide- or Tumor Necrosis Factor α-Stimulated Endothelial Cells via Activation of GPR41/43 and Inhibition of HDACs - Li, Meng; van Esch, Betty C. A. M.; Henricks, Paul A. J.; Folkerts, Gert; Garssen, Johan (Frontiers in Pharmacology, 2018)
Background and Aim: Previously, we found that short chain fatty acids (SCFA) inhibit LPS or TNFα-induced endothelial inflammatory responses and excessive vascular cell adhesion molecule-1 (VCAM-1) expression, two important steps in the development of atherosclerosis. However, the mechanisms involved are still unclear. We hypothesized that the effects of SCFA are associated with activation of G-protein coupled receptor 41/43 (GPR41/43) and/or inhibition of histone deacetylases (HDACs). Methods: The expression and location of GPR41/43 and HDAC3 in human umbilical vein endothelial cells (HUVEC) were confirmed. HUVEC were pre-incubated with acetate, butyrate or propionate alone or in combination with GLPG0974 (GLPG, antagonist of GPR43) or β-hydroxybutyrate (SHB, antagonist of GPR41) and then exposed to LPS or TNFα. Interleukin (IL)-6 and IL-8 levels and VCAM-1 expression were measured. HDAC activity was measured after treatment with butyrate, propionate and trichostatin (TSA, HDAC inhibitor). The peripheral blood mononuclear cell (PBMC) adhesive level was also determined after TSA treatment. Results: GPR41/43 were expressed on the membrane of HUVEC and HDAC3 was located in cytoplasm and nucleus. The GLPG and/or SHB treatments restored the inhibitory effects of acetate on IL-6 and IL-8 production and the inhibitory effects of butyrate or propionate on IL-6 production, but not on IL-8. In contrast, GLPG and/or SHB treatments did not affected the inhibitory effects of butyrate or propionate on TNFα-induced VCAM-1 expression. TSA showed similar effects on IL-8 production and VCAM-1 expression with butyrate and propionate. In addition, TSA significantly inhibited the adhesion of PBMC to an endothelial monolayer. Conclusion: Activation of GPR41/43 mediates the effects of acetate on IL-6 and IL-8 production and the effects of butyrate and propionate on IL-6 production. Furthermore, inhibition of HDACs mediates the effects of butyrate and propionate on IL-8 production, VCAM-1 expression and PBMC adhesion to endothelial monolayer. These data indicated the beneficial roles of SCFA in preventing vascular inflammation and relevant diseases by activation of GPR41/43 and inhibition of HDACs.